Plant extracts and essential oils in rabbit diet: A practical green-way for sustainable and resilient production systems - Pugliese, G; Losacco, C; Laudadio, V; Schiavitto, M; Tufarelli, V (Journal of the Hellenic Veterinary Medical Society, 2024)
Rabbits, integral to global agriculture, play a significant role in meat production in many developed and developing countries. As the demand for sustainable and natural farming practices rises, the utilization of plant extracts and essential oils in rabbit nutrition has garnered attention. Both plant extracts and essential oils offer multifaceted benefits in rabbit nutrition, positively impacting growth, digestion, and immune health. This comprehensive review consolidates the current understanding of the effects of plant extracts and essential oils on rabbit health and digestion, drawing from recent scientific literature. Emphasis is also placed on growth performance, nutrient utilization, immune response, and overall well-being. The outcomes underscore the practical significance of natural feed additives, paving the way for sustainable and resilient rabbit production systems.